A flow reactor study of NH3/DEE oxidation - Ruiz Gutiérrez, Adrián; Bello-Gallego, Álvaro; Alzueta , María U. (Jornada de Jóvenes Investigadores del I3A, 2025)
This study evaluates how dimethyl ether (DEE) affects the oxidation of ammonia. This compound improves the reactivity of NH3, reducing the temperature at which the chemical reaction begins. Likewise, a study is conducted on the different reaction routes that ammonia follows depending on various parameters.